El estudio de la infamia por medio del enunciado poético siniestro - Vargas Mora, Lorena (2019)
The sinister although it is striking and interesting at the literary level is quite difficult to investigate, however, you can find a way to approach it in the notion of sinister poetic statement as a discursive unit and as a conceptual axis of reading that moves through the text and provides knowledge about the background of the text. A way to demonstrate this has been the study and analysis of the novel Cruz de olvido (1999) by Carlos Cortés. In this article, based on the results of this research and on the reconsideration of other conceptual elements, we will expose how the sinister poetic statement provides some useful items for a more concrete approach to the scope of conceptual study of the sinister. In the same way we will try to make an approach to the manifestation of infamy.